Water quality monitoring system using Lora Network - Chan, Jian Siang; Azana Hafizah Mohd Aman; Mohd Syazwan Baharuddin; Attarbashi, Zainab S.; Mohamad Sirajuddin Jalil (Penerbit Universiti Kebangsaan Malaysia, 2024)
Environmental pollution has occurred over the past few decades. Air, water and soil pollution are the three main pollutions on Earth due to human negligence. Despite the rapid development of many technologies, new forms of pollution have emerged, including light and noise pollution. There are few attempts to make environmentally friendly products or raise awareness of the issue, but it has not always been successful. The difficulty of detecting water pollution makes it one of the pollutants that is challenging to manage. Some pollution, such as illegal oil dumping into the sea and oil spills, cannot be identified early and has harmful environmental effects that cannot be reversed. This can cause adverse effects not only on aquatic life but also on humans. Thus, this system was created to specifically deal with water pollution by obtaining data from pH, turbidity, and temperature sensors. The data will then be sent to the user's smartphone in real time over the LoRa network due to the network's ability to transmit data over long distances. Any abnormal data readings will be reported to the user, who may notify the authorities to immediately reduce any bad effects on the water.